Proceedings of the 2017 ACM Conference on Computer Supported Cooperative Work and Social Computing 2017
DOI: 10.1145/2998181.2998336
|View full text |Cite
|
Sign up to set email alerts
|

Assessing Behavior Stage Progression From Social Media Data

Abstract: Important work rooted in psychological theory posits that health behavior change occurs through a series of discrete stages. Our work builds on the field of social computing by identifying how social media data can be used to resolve behavior stages at high resolution (e.g. hourly/daily) for key population subgroups and times. In essence this approach opens new opportunities to advance psychological theories and better understand how our health is shaped based on the real, dynamic, and rapid actions we make ev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
23
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 39 publications
(23 citation statements)
references
References 68 publications
0
23
0
Order By: Relevance
“…For this study the options "never" and "yes, in the last year" were used. This selection was made contemplating the purpose of this study, taking into account the presence of factors and triggering moments for the use of substances at different times of the year, called "High-risk Time Periods", such as the new year and other holidays, 17 as well as periods in which there is an intense consumption of alcohol 18 and in summer holiday season 19 which allowed us to expand the possibilities of finding students who have had the substance use practices of interest for the present study. The ASSIST guide is also recommended for use in developing countries due to its reliability and validity.…”
Section: /11mentioning
confidence: 99%
“…For this study the options "never" and "yes, in the last year" were used. This selection was made contemplating the purpose of this study, taking into account the presence of factors and triggering moments for the use of substances at different times of the year, called "High-risk Time Periods", such as the new year and other holidays, 17 as well as periods in which there is an intense consumption of alcohol 18 and in summer holiday season 19 which allowed us to expand the possibilities of finding students who have had the substance use practices of interest for the present study. The ASSIST guide is also recommended for use in developing countries due to its reliability and validity.…”
Section: /11mentioning
confidence: 99%
“…For each of the behaviors, Tweets were classified hierarchically into behavior versus not behavior related, then first person versus not first person (the person Tweeting is talking about themselves performing the action). Finally, to isolate episodes of consuming alcohol or tobacco that are linked to precise times, for each pipeline the Tweets were classified into past, present, and future following previous work identifying behavior stages from social media [53]. As we are interested in self-reported communications of behaviors linked to time, we used data from the “present” category of the last classification for further analyses in this paper.…”
Section: Data Preprocessingmentioning
confidence: 99%
“…For both behaviors, due to the low percentage of behavior-specific Tweets, as well as the nuanced differences between marijuana and tobacco, the training (labelled) data was very carefully curated and we used active learning following the approach in [53]. First, we developed a dictionary, using Internet sources such as Urban dictionary and Wikipedia as references to pre-filter Tweets that would be submitted for manual labeling, in order to increase instances of target classes.…”
Section: Data Preprocessingmentioning
confidence: 99%
See 1 more Smart Citation
“…Online social communities constitute a significant presence in our lives. Researchers and practitioners are using online data to illuminate many aspects of life including health, politics and culture, based on what people post [1][2][3][4][5]. For example, some studies have focused on recipe websites and shown how food names in online recipes can be a proxy for consumption and dietary patterns of individuals [6].…”
Section: Introductionmentioning
confidence: 99%